Informal workplace learning among novice teachers :a study in Kuching division, Sarawak - Ki, Yen Ping. (Universiti Malaysia Sarawak, UNIMAS, 2010)
The purpose of this study was to investigate the types of informal learning activities that the novice teachers in Kuching Division engaged in at work and the level of novice teachers’ engagement in informal learning activities. More specifically, this study explored the individual and organizational factors affecting novice teachers’ engag ement in informal learning activities, the relationship between level of informal learning engagement and organizational culture in school, and the differences in the level of novice teachers’ engagement in informal learning activities based on gender. This study was a cross-sectional survey research. A total of 85 usable questionnaires were returned out of 100 questionnaires distributed to the randomly selected novice teachers from ten schools in Kuching Division. Findings in this study showed that novice teachers were only moderately involved in workplace informal learning activities. The findings also showed moderate but significant positive relationship between school culture and the level of informal learning engagement among novice teachers. However, there was no significant difference between males and females novice teachers in the level of engagement in workplace informal learning. In addition, the findings also indicated that novice teachers learnt most frequently from their own ivtrial and erroractivities. Novice teachers’ informal learning activities were mostly influenced by their interest in the current professional field and job environment. The findings of this study including the various activit ies and factors that influence informal learning engagement are useful to human resource development practitioners for prioritizing informal learning interventions. Furthermore, there is currently little local empirical research on the individual learning and learning organization concept. Thus, this research can also address the gap especially through its findings on the relationship between informal learning engagement level and organizational learning culture in school.